Patients, personnel and profits : improving healthcare for international patients - Dorna, Thijs; Koene, Bas, 1966-; Martín, Fuensanta (London : Rotterdam School of Management, Erasmus University, 2018)
Juan Alvarez, manager of the private hospital HS in Malaga, Spain, recently implemented a change in how it is treating its international patients, after they complained about the quality of care at the hospitals. Previously, the hospital used a standard somatic medical approach - placing international patients across various wards depending on the type of medical care required. To cater for their specific needs there were two options for the hospital: special treatment of the international patients in the existing structure, or concentrating the international patients in one place to more easily/more effectively cater to their needs. The hospital has chosen the latter approach, placing the international patients in a separate ward, irrespective of their medical needs. The hospital is a relatively new private hospital (founded in in 2009). The introduction of the International ward was quite successful, reflected in increasing referrals of international patients to the hospital and relatively positive responses by the staff affected in the hospital. Due to its positive impact on Job Quality for those involved it also offers opportunities for further expansion.
Originally Published InDorna, T., Koene, B., & Martín, F. (2018). Patients, Personnel and Profits: Improving healthcare for international patients. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Hospitals -- Administration -- Case studies